Provision of pharmaceutical care in patients with limited English proficiency: Preliminary findings - Devinder Singh Arora; Amary Mey; Satish Maganlal; Sohil Khan (Wolters Kluwer Medknow Publications, 2015)
Objective: Overcoming language and cultural barriers is becoming ever challenging for pharmacists as the patient population grows more ethnically diverse. To evaluate the current practices used by the pharmacists for communicating with patients with limited English proficiency (LEP) and to assess pharmacists' knowledge of, attitude toward, and satisfaction with accessing available services for supporting LEPs patients within their current practice settings. Methods: Semi-structured interviews were conducted with five pharmacists employed in pharmacies representing multiple practice settings Queensland, Australia. Thematic analysis was primarily informed by the general inductive approach. NVivo software (QSR International Pty Ltd.) was used to manage the data. Findings: Three interlinked themes emerged from the analysis of interview data: (1) Barriers to the provision of pharmaceutical care, (2) Strategies employed in dealing with LEP patients, and (3) Lack of knowledge about existing services. Pharmacists recognized their lack of skills in communicating with LEP patients to have potential negative consequences for the patient and discussed these in terms of uncertainty around eliciting patient information and the patient's understanding of their instructions and or advice. Current strategies were inconsistent and challenging for LEP patient care. While the use of informal interpreters was common, a significant degree of uncertainty surrounded their actual competency in conveying the core message. Conclusion: The present study highlights a significant gap in the provision of pharmaceutical care in patients with LEP. Strategies are needed to facilitate quality use of medicines among this patient group.